Technical efficiency of Vietnamese manufacturing firms: do FDI spillovers matter? - Nguyen, Canh; Le, Minh; Cai, Khoa; Simioni, Michel (Journal of Business Economics and Management, 2021)
This paper investigates the spillover effect (backward, forward, and horizontal linkage) of foreign direct investment (FDI) firms on the technical efficiency of local firms. This research extends the literature by employing meta-frontier framework analysis which is superior to single stochastic analysis because each industry has a different combination of inputs (or dissimilar production technology). Using a large data set (178,700 firm-year observations), this paper finds evidence on the negative impact of the horizontal and forward linkages on the meta-technical inefficiency for the data set as a whole as well as in three economic regions, in private owned firms, and capital and labor-intensive sectors in Vietnam.